Gender and the city in Euripides' political plays - Mendelsohn, Daniel Adam 1960- (Oxford University Press, 2007)
Daniel Mendelsohn makes use of insights into classical Greek conceptions of gender and Athenian notions of civic identity to demonstrate that the plays 'Children of Herakles' and 'Suppliant Women' by Euripides are subtle and coherent exercises in political theorizing.